Identification of Multiple Phosphorylation Sites on Maize Endosperm Starch Branching Enzyme IIb, a Key Enzyme in Amylopectin Biosynthesis - Makhmoudova, Amina (American Society for Biochemistry and Molecular Biology, 2014)
Starch branching enzyme IIb (SBEIIb) plays a crucial role in amylopectin biosynthesis in maize endosperm by defining the structural and functional properties of storage starch and is regulated by protein phosphorylation. Native and recombinant maize SBEIIb were used as substrates for amyloplast protein kinases to identify phosphorylation sites on the protein. A multidisciplinary approach involving bioinformatics, site-directed mutagenesis, and mass spectrometry identified three phosphorylation sites at Ser residues: Ser(649), Ser(286), and Ser(297). Two Ca(2+)-dependent protein kinase activities were partially purified from amyloplasts, termed K1, responsible for Ser(649) and Ser(286) phosphorylation, and K2, responsible for Ser(649) and Ser(297) phosphorylation. The Ser(286) and Ser(297) phosphorylation sites are conserved in all plant branching enzymes and are located at opposite openings of the 8-stranded parallel β-barrel of the active site, which is involved with substrate binding and catalysis. Molecular dynamics simulation analysis indicates that phospho-Ser(297) forms a stable salt bridge with Arg(665), part of a conserved Cys-containing domain in plant branching enzymes. Ser(649) conservation appears confined to the enzyme in cereals and is not universal, and is presumably associated with functions specific to seed storage. The implications of SBEIIb phosphorylation are considered in terms of the role of the enzyme and the importance of starch biosynthesis for yield and biotechnological application.